Characteristics of the Inflammatory Bowel Disease in Children: A Croatian Single-Centre Retrospective Study - Ivan Pivac; Antonia Jelicic Kadic; Ranka Despot; Vanda Zitko; Darija Tudor; Edita Runjic; Josko Markic (MDPI AG, 2023)
Inflammatory bowel diseases (IBDs), encompassing ulcerative colitis (UC) and Crohn's disease (CD), are chronic gastrointestinal disorders often diagnosed in youth, presenting unique features compared to adult-onset cases. We aimed to profile pediatric IBD patients in Croatia through a retrospective analysis of children up to 18 years old diagnosed with IBD at the University Hospital of Split from 1 January 2012, to 31 December 2021, utilizing data collected during hospitalization for diagnosis. Over a decade, 107 children were diagnosed, with 43.9% having UC, 55.1% CD, and 0.9% IBD-unclassified. Median age at diagnosis was 14.1 years, with UC patients being older (14.8 vs. 13.7 years, p = 0.044). Males constituted 60.7% of patients. Median symptom duration was 2.0 months, with CD patients experiencing a longer diagnostic delay (3.0 vs. 2.0 months, p = 0.003). The median incidence rate was 9.89 (95% CI 5.93-13.84) per 100,000 children/year, varying across age groups. Median (IQR) BMI z-score was −0.34 (−0.97-0.45). Common symptoms included diarrhea (60.7%) and abdominal pain (50.5%), with rectal bleeding more prevalent in UC (72.3% vs. 32.2%, p < 0.001). While our study offers valuable insights into pediatric IBD in Croatia, further prospective research is needed to clarify disease progression and development.